Association of the MUC5B promoter polymorphism with idiopathic pulmonary fibrosis in a lebanese cohort - Mouawad, Antoine; Chouery, Eliane; Chebly, Alain; Salem, Nabiha; Corbani, Sandra; Safieddine, Maissa; Dabar, Georges (Frontiers in Genetics, 2025)
Background and objectiveIdiopathic Pulmonary Fibrosis (IPF) is an interstitial lung disease that causes irreversible alterations in the architecture of the lung parenchyma, leading to impaired ventilation. Both environmental factors and genetic predisposition play significant roles in the development of IPF. A single nucleotide polymorphism (SNP) (rs35705950) within the promoter of the mucin 5B gene (MUC5B) has been reported to be associated with the disease; however, no data is available from Lebanon or the Middle East. This study aims to identify the frequency of the MUC5B promoter variant among a cohort of Lebanese IPF patients, compare it to the general population and assess its association with the risk of developing the disease.MethodsA total of 55 patients diagnosed with IPF, according to the ATS/ERS criteria, and 94 healthy controls were included in the study. DNA samples were extracted and genotyped for the MUC5B promoter polymorphism by Sanger sequencing. Descriptive statistics were performed on clinical characteristics. Pearson’s chi-squared and T-student tests were performed to determine statistical significance. Odds ratios quantified genetic variant associations with IPF.ResultsThe MUC5B SNP rs35705950 was significantly more frequent in IPF patients compared to the control group, in both heterozygous and homozygous forms. Additionally, a significant association was found between the variant and susceptibility to IPF.ConclusionThis study shows that the MUC5B polymorphism rs35705950 is significantly more frequent in the Lebanese IPF population compared to the control group and is associated with an increased risk of developing IPF.